PROFESSIONAL STANDARD AND FEDERAL STATE EDUCATIONAL STANDARD FOR UNDERGRADUATE PROGRAMS - V. A. PROKHOROV (Высшее образование в России, 2018)
Abstract.Undergraduate educational programs making on the basis of professional standards compliance does not meet the strategic goal of vocational education system reforming – training personnel capable of making modern competitive products and services affecting the country’s innovative development. The disadvantage of the former higher education system is not the professional competencies lack in the education content, but the lack of graduates’ innovative competencies. The undergraduate federal state educational standard making on the principle of vocational guidance is proposed in the paper. Professional education should become an ongoing process in modern conditions and higher education at undergraduate level has to be professionally oriented, universal, and invariant from the constantly emerging changes in the social world. There is supported a statement that if the lifelong learning programs variety is a tool for short-term tasks solving in the production and provision of operational upgrading, then higher education at undergraduate level is an instrument of the medium-term training personnel strategy.